-3x+2(-2-2x)=3-7x

Simple and best practice solution for -3x+2(-2-2x)=3-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+2(-2-2x)=3-7x equation:


Simplifying
-3x + 2(-2 + -2x) = 3 + -7x
-3x + (-2 * 2 + -2x * 2) = 3 + -7x
-3x + (-4 + -4x) = 3 + -7x

Reorder the terms:
-4 + -3x + -4x = 3 + -7x

Combine like terms: -3x + -4x = -7x
-4 + -7x = 3 + -7x

Add '7x' to each side of the equation.
-4 + -7x + 7x = 3 + -7x + 7x

Combine like terms: -7x + 7x = 0
-4 + 0 = 3 + -7x + 7x
-4 = 3 + -7x + 7x

Combine like terms: -7x + 7x = 0
-4 = 3 + 0
-4 = 3

Solving
-4 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4a-6=-36 | | 21x+6=17x+32 | | 2(w+3)+2w=42 | | 6(4-2h)=4(5-3h) | | 3y+9= | | -9(d+2)=4(15+d) | | 90+x=125 | | -2(16-3p)=-5p+1 | | 2-y=1 | | -50t-5=70 | | 6-9= | | 80+x=95 | | X-0=1 | | -11x-3x=10-10x | | 3(-z+12)=4(z-5) | | 2x-5+3x=5 | | 5-6x=3(1-2x) | | 3n+6=87 | | Z^2-20z-21=0 | | 5y=3(y-2) | | -21=-5v+3(v-5) | | 3b+16=40 | | -16-9-4x=-9 | | =1+1 | | 8x+20=2x+20 | | -5=6n | | 5-3x+2=4x+7 | | 4x^2-23x+13=-7x+6 | | 24-6m=0 | | .5(10z+8)-2=4(z-6) | | 8+9x=-6 | | 2(x+3)=5+2x |

Equations solver categories